MicroRNA-16, via FGF2 Regulation of the ERK/MAPK Pathway, Is Involved in the Magnesium-Promoted Osteogenic Differentiation of Mesenchymal Stem Cells - Qi, Hong (Oxid Med Cell Longev, 2020)
microRNAs (miRNAs) participate in the osteogenic differentiation of bone marrow mesenchymal stem cells (BMSCs). However, few reports have discussed the effect of miRNAs on the magnesium chloride (MgCl(2))-induced promotion of osteogenic differentiation of BMSCs, a process involved in the healing of bone tissue. As determined in the present investigation, MgCl(2) decreased miR-16 levels; increased levels of fibroblast growth factor 2 (FGF2), p-p38, and p-ERK; and promoted the osteogenic differentiation of BMSCs. Enhancement of miR-16 levels by an miR-16 mimic blocked these MgCl(2)-induced changes. Moreover, luciferase reporter assays confirmed that miR-16 binds to the 3′UTR region of FGF2 mRNA. Down-regulation of FGF2 blocked the MgCl(2)-induced increases of p-p38 and p-ERK and the promotion of the osteogenic differentiation of BMSCs. Furthermore, over-expression of miR-16 attenuated the MgCl(2)-induced overproduction of p-p38 and p-ERK1/2 and the high levels of osteogenic differentiation, effects that were reversed by elevated expression of FGF2. In summary, the present findings provide a mechanism by which miR-16 regulates MgCl(2)-induced promotion of osteogenic differentiation by targeting FGF2-mediated activation of the ERK/MAPK pathway.